Association between serum levels of insulin‐like growth factor‐1, bioavailable testosterone, and pathologic Gleason score. (10th July 2018) - Kim, Myong; Kim, Jong Won; Kim, Jong Keun; Lee, Sang Mi; Song, Cheryn; Jeong, In Gab; Hong, Jun Hyuk; Kim, Choung‐Soo; Ahn, Hanjong
Abstract: Background: We evaluated the association between serum levels of insulin‐like growth factor‐1 (IGF‐1), bioavailable testosterone, and surgical Gleason score (GS). Methods: We analyzed 793 patients who underwent radical prostatectomy and 272 men with negative prostate biopsy. Serum levels of IGF‐1 and testosterone were measured before surgery or biopsy. Results: The mean IGF‐1 levels of prostate cancer patients and men with a negative biopsy were 143.8 and 118.9 ng/mL, respectively ( P  <   0.001). Men with high serum IGF‐1 were more likely to have prostate cancer (highest vs lowest quartile, odds ratio [OR] = 3.35; P trend  < 0.001). However, among men with prostate cancer, the mean IGF‐1 levels of those with low (GS ≤ 6), intermediate (GS = 7), and high surgical GS (GS ≥8) were 151.7, 144.1, and 132.9 ng/mL, respectively ( P  <   0.001). Using quartile analysis, high serum IGF‐1 levels were shown to be associated with a low risk of high surgical GS (OR = 0.464; P trend  = 0.006). Serum bioavailable testosterone concentration was positively correlated with serum IGF‐1 level ( r  =   0.157, P  <   0.001). High bioavailable testosterone level was also associated with a low risk of high surgical GS in patients without diabetes mellitus (OR = 0.569; P trend  = 0.040). Among men with biopsy GS ≤ 3 + 4 ( n  =   460), upgrading to high surgical GS was more frequent in patients with low IGF‐1 level (≤116.0 ng/mL; 9.9%) or low bioavailable testosterone level (≤0.85 ng/mL; 9.3%) than in patients with normal IGF‐1 and bioavailable testosterone levels (2.6%; P  =   0.004). Conclusions: Serum levels of IGF‐1 and bioavailable testosterone show inverse associations with high surgical GS. This suggests that high‐grade prostate cancer develops independently of these two substances. Abstract : High serum insulin‐like growth factor‐1 level (odds ratio [OR] = 0.464; P trend  = 0.006) and high bioavailable testosterone level (OR = 0.464; P trend  = 0.006) were associated with a low risk of high pathologic Gleason score. This suggests that high‐grade prostate cancer has autonomy for these two substances in relation to tumorigenesis.